Effects of nerve-sparing procedures on surgical margins after robot-assisted radical prostatectomy. Issue 12 (9th September 2022) - Yang, Ching-Wei; Wang, Hsiao-Hsien; Fayez Hassouna, Mohamed; Chand, Manish; Huang, William J.; Chung, Hsiao-Jen
Abstract : Background: Nerve-sparing (NS) techniques could potentially increase positive surgical margins after robot-assisted radical prostatectomy (RARP). Nevertheless, the available studies have revealed ambiguous results among distinct groups. This study purposed to clarify the details of NS techniques to accurately estimate their influence on margin status. Methods: We studied RARPs performed by one surgeon from 2010 to 2018. Surgical margins were evaluated by the laterality and levels of NS techniques in site-specific prostate lobes. The multivariable analysis evaluated the effects of nerve-sparing procedures, combined with other covariate factors, on margin status. Results: Overall, 419 RARPs involving 838 prostate lobes were analyzed. Notably, 181 patients (43.4%) had pT2-stage, and 236 (56.6%) had pT3-stage cancer. The PSM rates for patients who underwent unilateral, bilateral, and non NS procedures were 30.3%, 28.8%, and 50%, respectively ( p = 0.233) or in stratification by pT2 ( p = 0.584) and pT3 ( p = 0.116) stage. The posterolateral PSM rates among site-specific prostate lobes were 10.9%, 22.4%, and 18.9% for complete, partial, and non NS techniques, respectively ( p = 0.001). The partial NS group revealed a significant increase in PSM rate compared with the complete NS (OR 2.187, 95% CI: 1.19–4.03) and non NS (OR 2.237, 95% CI: 1.01–4.93) groups in site-specific prostate lobes. Conclusion: Partial NS procedures have a potential risk of increasing the positive surgical margins rate than complete and non NS procedures do. Therefore, correct case selection is required before performing partial NS techniques.